(In)visible monsters the theory and praxis of horror in Philippine short fiction in English - Tan, Yvette Natalie U. (2005)
This thesis studies horror in Philipine short fiction in English, specifically the works of National Artists Francisco Arcellana, N.V.M. Gonzales, Nick Joaquin, F. Sison Jose, Edith Tiempo and Jose Garcia Villa. Most of the works of the authors mentioned are written in the realist mode, seemingly devoid of the trappings of the horror genre. There are no dark castles, blood-sucking figures, or consumptive damsels in distress. The researcher believes that even though the traditional characteristics of a horror story are not present in most of the stories analyzed, they nevertheless contain elements and images of horror, even of only in the character's minds. The thesis has the following objectives: A method of analysis, which was first applied to horror film, is applied not only to a completely different medium, that is, short fiction. In analyzing the chosen literary texts, this method of analysis yields a different way of looking at Philippine short fiction and culture, as defined by our literature in English. The analysis also explores areas and problems germane to feminism by focusing on aspects of the texts that deal with its portrayal of its feminine characters of the feminization of personalities, places, events and so forth; as well as other things that situates them in the abject. Not only does this method of analysis pick apart what troubles the story it is tackling, but it may also point out concerns (individual, family, social and cultural values) that the writers or society faced. In this context, the thesis serves as a springboard for cultural studies. The study has revealed some enlightening facts about our culture, namely images of horror that can be grouped into the following categories:Ethnic-Native Practices;Western Practices and; the other stories fall under the category of contemporary horrors, images that went undetected before but have become significant in today's postmodern world. This method of analysis therefore shows us another way of perceiving the world in this age of globalization. The study therefore elevates the status of the horror genre in the Philippine academe as a literature that goes beyond pulp. In fact, this study has shown that it is a genre that has a lot to say about the human condition and about his culture, albeit using different conventions that, given their detachment from reality, have the power to both suppress or liberate the people who write them, the people who read them, and the society they reflect.
Thesis (M.A. Comparative Literature)--University of the Philippines Diliman.
Keywords: Horror tales, Philippine (English) -- History and criticism; Horror in literature; Monsters in literature; Feminism and literature; Feminist fiction